Altered peptide ligands of myelin basic protein (MBP87-99) conjugated to reduced mannan modulate immune responses in mice - Katsara, M.; Yuriev, E.; Ramsland, Paul; Tselios, T.; Deraos, G.; Lourbopoulos, A.; Grigoriadis, N.; Matsoukas, J.; Apostolopoulos, V. (2009)
Mutations of peptides to generate altered peptide ligands, capable of switching immune responses from T helper 1 (Th1) to T helper 2 (Th2), are promising candidates for the immunotherapy of autoimmune diseases such as multiple sclerosis (MS). We synthesized two mutant peptides from myelin basic protein 87-99 (MBP87-99), an immunodominant peptide epitope identified in MS. Mutations of residues K91 and P96, known to be critical T-cell receptor (TCR) contact sites, resulted in the mutant peptides [R91, A96]MBP87-99 and [A 91, A96]MBP87-99. Immunization of mice with these altered peptide ligands emulsified in complete Freund's adjuvant induced both interferon-? (IFN-?) and interleukin-4 (IL-4) responses compared with only IFN-? responses induced to the native MBP 87-99 peptide. It was of interest that [R91, A 96]MBP87-99 conjugated to reduced mannan induced 70% less IFN-? compared with the native MBP87-99 peptide. However, [A91, A96]MBP87-99 conjugated to reduced mannan did not induce IFN-?-secreting T cells, but elicited very high levels of interleukin-4 (IL-4). Furthermore, antibodies generated to [A91, A96]MBP87-99 peptide conjugated to reduced mannan did not cross-react with the native MBP87-99 peptide. By molecular modelling of the mutant peptides in complex with major histocompatibility complex (MHC) class II, I-As, novel interactions were noted. It is clear that the double-mutant peptide analogue [A91, A96]MBP 87-99 conjugated to reduced mannan is able to divert immune responses from Th1 to Th2 and is a promising mutant peptide analogue for use in studies investigating potential treatments for MS. © 2009 Blackwell Publishing Ltd.